2013
DOI: 10.1088/0004-637x/778/1/59
|View full text |Cite
|
Sign up to set email alerts
|

NON-THERMAL X-Rays AND INTERSTELLAR GAS TOWARD THE Γ-Ray SUPERNOVA REMNANT RX J1713.7–3946: EVIDENCE FOR X-Ray ENHANCEMENT AROUND CO AND H I CLUMPS

Abstract: RX J1713.7−3946 is the most remarkable very-high-energy γ-ray supernova remnant which emits synchrotron X-rays without thermal features. We made a comparative study of CO, Hi and X-rays in order to better understand the relationship between the X-rays, and the molecular and atomic gas.The results indicate that the X-rays are enhanced around the CO and Hi clumps on a pc scale but are decreased inside the clumps on a 0.1 pc scale. Magnetohydrodynamic numerical simulations of the shock interaction with molecular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 58 publications
11
87
0
Order By: Relevance
“…The clumps that survive the stellar wind and remain embedded in the cavity are characterized by a subparsec size, Lc = 0.1 Lc,−1 pc, and a large density, nc 10 3 nc,3 cm −3 (see the simulations by Inoue et al 2012 and the observations by Fukui et al 2012 andSano et al 2013).…”
Section: Dynamical Evolution Of the Snrmentioning
confidence: 99%
“…The clumps that survive the stellar wind and remain embedded in the cavity are characterized by a subparsec size, Lc = 0.1 Lc,−1 pc, and a large density, nc 10 3 nc,3 cm −3 (see the simulations by Inoue et al 2012 and the observations by Fukui et al 2012 andSano et al 2013).…”
Section: Dynamical Evolution Of the Snrmentioning
confidence: 99%
“…Studies of the ISM in SNR environments have improved our understanding of SNR evolution, shock heating/ionization, acceleration of CRs, and high-energy radiation (e.g., Fukui et al 2012;Inoue et al 2012;Yoshiike et al 2013;Sano et al 2013). In RCW 86, however, deep studies of the ISM have not been reported.…”
mentioning
confidence: 99%
“…(1) Hadronic model based on MHD simulations: The shock interaction with dense clouds excites turbulence, which amplifies the magnetic field up to the mG order (Inoue et al 2012;Sano et al 2013Sano et al , 2015. These results may be crucial for our better understanding of the gamma-ray and X-ray images of SNRs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Although weak thermal X-ray emission has recently been detected from the SNR interior (Katsuda et al 2015), the X-ray emission is still dominated by synchrotron radiation, which links directly to the existence of high-energy electrons. Radio observations of CO and H I gas have revealed a highly inhomogeneous medium surrounding the SNR, such as clumpy molecular clouds (Fukui et al 2003Fukui 2013;Moriguchi et al 2005;Sano et al 2010Sano et al , 2013Sano et al , 2015. Another radio observation of CS also confirmed the existence of a very dense (>10 5 cm −3 ) ISM core toward the SNR (Maxted et al 2012).…”
Section: Origin Of Gamma Rays From Snr Rxj17137−3946mentioning
confidence: 94%
See 1 more Smart Citation